Hierarchical control strategy for a three-phase 4-wire microgrid under unbalanced and nonlinear load conditions - Naderipour A.; Abdul-Malek Z.; Ramachandaramurthy V.K.; Kalam A.; Miveh M.R. (ISA - Instrumentation, Systems, and Automation Society, 2023)
Frequency stability; Reactive power; Restoration; Software testing; Transient analysis; Voltage control; DigSILENT power factories; Fast transient response; Hierarchical control; Islanded mode; Micro grid; Nonlinear load; Reactive power compensator; Total harmonic distortion (THD); Electric power system control